PENCEGAHAN STUNTING MELALUI KEGIATAN TEMATIK “ISI PIRINGKU DENGAN MAKANAN BERGIZI” DI DESA SITIREJO BLORA - Siti Amaroh; Naila Uswatun Hasanah; Masturin (PRAXIS: Jurnal Pengabdian kepada Masyarakat, 2025)
Stunting is a pressing public health issue in developing countries. This community service activity was conducted in Sitirejo Village, Blora Regency, Central Java Province. The program was carried out as part of the Integrated Community Service for Religious Moderation Competency (KKN-IKMB) with the theme "My Plate with Nutritious Food" to raise community awareness about stunting prevention. The activities were implemented through interactive community education, animated song and video screenings, simulations, and nutritious food processing using local resources. The program involved the village midwife, posyandu cadres, and local residents, and was held at the residence of a village official. The program was deemed effective in enhancing the community's understanding of balanced nutrition and the utilization of local potential. Educational media, such as songs and animated videos, successfully captured attention and improved participants' knowledge. Additionally, mothers, particularly those with young children, were able to understand and practice preparing nutritious meals to support optimal child development. The results indicate that community-based education integrated with advances in information technology can serve as an effective strategy to help reduce the prevalence of stunting at the village level. The utilization of local resources also presents opportunities for further development, ensuring that nutritional needs can be met more easily and affordably.